1993
DOI: 10.1039/ft9938901079
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of supported iron oxide studied by temperature-programmed reduction combined with mössbauer spectroscopy and X-ray diffraction

Abstract: The reduction of iron oxide supported on alumina, anatase and rutile and the interactions between iron oxides and these supports have been studied using temperature-programmed reduction, Mossbauer spectroscopy and X-ray diffraction. The intermediates formed during reduction depend strongly on the nature of the support, the iron loading and the reduction conditions used. Several iron species such as bulk a-Fe,O,, superparamagnetic a-Fe203 and surface iron-aluminium oxides are found in the alumina-supported iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…It is pertinent to note that the ratio of the iron cations in octahedral to those in tetrahedral sites (parameter S), estimated by peak areas, was observed to decrease to a value of 1.5, as compared to a value of 2 for pure Fe 3 O 4 , indicating that there were more iron cations in tetrahedral sites in this sample than in pure Fe 3 O 4 . From the comparison of this behavior with the results of Topsøe et al, 26 Lund et al 21 and Gao et al 27 in their studies on magnetite-supported lead, silica-supported magnetite and titania-supported magnetite, it is suggested that the iron cations in octahedral sites in the first reduction stage of the In-Fe 2 O 3 /HZSM-5(I) catalyst were substituted by indium cations, resulting in the decrease in S. After the sample was treated at 630 C, the spectrum showed a doublet with parameters typical of high-spin Fe 2+ in tetrahedral vacancies, 16,28,29 a typical sextuplet of a-Fe and a singlet which possibly resulted from the small particles of metallic iron. 30,31 Since pure wustite is thermodynamically unstable at room temperature, 22,32 and the interaction between indium oxide and iron oxide was weak in the In-Fe 2 O 3 /HZSM-5(I) catalyst, the existence of stable ferric cations was apparently caused by the interaction between the iron oxide and the HZSM-5 support.…”
Section: Resultsmentioning
confidence: 99%
“…It is pertinent to note that the ratio of the iron cations in octahedral to those in tetrahedral sites (parameter S), estimated by peak areas, was observed to decrease to a value of 1.5, as compared to a value of 2 for pure Fe 3 O 4 , indicating that there were more iron cations in tetrahedral sites in this sample than in pure Fe 3 O 4 . From the comparison of this behavior with the results of Topsøe et al, 26 Lund et al 21 and Gao et al 27 in their studies on magnetite-supported lead, silica-supported magnetite and titania-supported magnetite, it is suggested that the iron cations in octahedral sites in the first reduction stage of the In-Fe 2 O 3 /HZSM-5(I) catalyst were substituted by indium cations, resulting in the decrease in S. After the sample was treated at 630 C, the spectrum showed a doublet with parameters typical of high-spin Fe 2+ in tetrahedral vacancies, 16,28,29 a typical sextuplet of a-Fe and a singlet which possibly resulted from the small particles of metallic iron. 30,31 Since pure wustite is thermodynamically unstable at room temperature, 22,32 and the interaction between indium oxide and iron oxide was weak in the In-Fe 2 O 3 /HZSM-5(I) catalyst, the existence of stable ferric cations was apparently caused by the interaction between the iron oxide and the HZSM-5 support.…”
Section: Resultsmentioning
confidence: 99%
“…For iron catalysts supported on Al 2 O 3 and SiO 2 the formation of ferrous aluminates and silicates has been reported [18,[20][21][22][23][24]. Wielers et al [21] observed the formation of a silicate layer during reduction of trivalent iron indicating that, as soon as divalent iron is formed, iron migrates into the support.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Mössbauer measurements reveal the presence of high spin Fe 2+ species with quadrupole splittings at room temperature (2.7-1.7 mm/s) significantly higher than for bulk FeO (about 0.55 mm/s). These results point to the formation of ferrous species due to an intimate interaction with the support [9][10][11][13][14][15]18,[20][21][22][23][24]. One of the two iron(II) species is identified as a Fe 2+ which upon formation immediately migrates into the zirconia support to form a mixed oxide.…”
Section: Reduction and Reduction Model Of Fe/zromentioning
confidence: 99%
See 2 more Smart Citations